IMPLEMENTATION OF GREEN OPEN SPACE MANAGEMENT AREA OF SETTLEMENT IN GAJAHMUNGKUR DISTRICT, SEMARANG CITY - Yeremia Toni Marpaung; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2019)
The existing development in big cities must be balanced with the preservation of the surrounding environment. Environmental preservation is one of the characteristics of sustainable development. The development that doesn’t only pay attention to the present but also the future. Gajahmungkur Subdistrict is an area that has not fulfilled the minimum percentage of green open space in Semarang City. Problems that arise : How is the implementation of green open space arrangement area of settlement in Gajahmungkur District? What are the factors that influence the implementation of the green open space arrangement area of settlement in the Gajahmungkur District? The purpose of the study is to analyze the implementation of the arrangement of green open space in the Settlement Area in Gajahmungkur District, Semarang City and to find out the factors that influence the implementation of the public green open space arrangement in Gajahmungkur District, Semarang City.The researcher focused on the implementation of the arrangement of settlement area green open space through the use of green open space in the center of the environment, the use of green space on the roadside and the use of green space on the yard / housing yard by taking into account communication, resources. The researcher used descriptive qualitative research methods. The technique used in selecting informants with snowball technique.The results showed that the implementation of Green Open Space in settlement area arrangement in Gajahmungkur Subdistrict had not gone well. There are still many areas in Gajahmungkur Subdistrict that do not meet the requirements of green open space, especially in green open space area in the Environment Center. One of the main causes is poor communication. The intended communication is that there is a lack of good transmission of policies so that there are still many target groups of people who do not know about green open space management, especially through utilization activities. It is recommended to further improve communication with each target group by conducting community socialization on Green Open Space structuring policies in the Settlement Area so that the community understands the importance of Green Open Space in Settlement areas